Variations of Gastrocolic Trunk of Henle and Its Significance in Gastrocolic Surgery - Yuan Gao; Yun Lu (Gastroenterology Research and Practice)
Due to the increasing incidence of gastrointestinal (GI) tumors, more and more importance is attached to radical resection and patients’ survival, which requires adequate extent of resection and radical lymph node dissection. Blood vessels around the gastrointestinal tract, as anatomical landmarks for tumor resection and lymph node dissection, play a key role in the successful surgery and curative treatment of gastrointestinal tumors. In the isolation of subpyloric area or hepatic flexure of the colon for gastrectomy or right hemicolectomy, lymph node dissection and ligation are often performed at the head of the pancreas and superior mesenteric vein, during which even a minor inadvertent error may lead to unwanted bleeding. Among these blood vessels, the venous system composed of Henle’s trunk and its tributaries is the most complex, which has a direct influence on the outcome and postoperative recovery of the patients. There are many variations of Henle’s trunk, with complicated courses and various locations, attracting more and more researchers to study it and tried to analyze the influence of its variations on gastrointestinal surgeries. We characterized various variants and tributaries of Henle’s trunk using autopsy, vascular casting, 3D CT reconstruction, intraoperative anatomy, and Hisense CAS system and summarized and analyzed the tributaries of Henle’s trunk, to determine its influence on GI surgeries.